Operational maintenance practice of escalator in commercial building / Muhammad Hanafi Hairudin and Irwan Mohammad Ali - Hairudin, Muhammad Hanafi; Mohammad Ali, Irwan (2023)
The escalator is essential for moving people from one location to another. Nonetheless, several mishaps using escalators have been documented. These can arise as a result of a lack of maintenance, which causes system breakdowns, inadequate safety procedures, wear and tear, user carelessness, and other factors. This study aimed to assess escalator maintenance operations in commercial buildings, focusing on the Perak area through two case studies. Questionnaire data was collected using a Google Form and analyzed using SPSS Software to understand maintenance activities and costs to ensure rigor. The finding revealed that inadequate maintenance, inconsistent safety measures, and wear and tear contribute to escalator malfunctions and accidents. To address this, it is recommended that building owners prioritize regular maintenance, implement robust safety protocols, consider technological upgrades, and promote user knowledge. As one of the most significant ways of entry in a building, it is critical to improve the efficiency of escalators, particularly in commercial buildings. Hence, such measures can enhance escalator efficiency, reduce accidents, and contribute to safer commercial building environments.